2020
DOI: 10.7759/cureus.6570
|View full text |Cite|
|
Sign up to set email alerts
|

The Perception of Coronary Artery Disease and Cardiac Catheterization in Saudi Arabia: “What the Public Know”

Abstract: Objective Coronary artery disease (CAD) constitutes a significant health hazard in middle-aged individuals in Saudi Arabia. We sought to assess the level of knowledge of cardiovascular risk factors and describe the perception of coronary intervention among the general population in the city of Jeddah in the western part of Saudi Arabia. Methods A cross-sectional study was conducted in the city of Jeddah during the period from April 2019 to September 1, 2019, by using a structured online questionnaire to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…This result is consistent with other studies done in the region and other developing countries in Africa and East Asia. [ 8 10 11 12 13 14 ] Better results were, however, portrayed in similar studies done in developed countries. [ 15 16 ]…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This result is consistent with other studies done in the region and other developing countries in Africa and East Asia. [ 8 10 11 12 13 14 ] Better results were, however, portrayed in similar studies done in developed countries. [ 15 16 ]…”
Section: Discussionmentioning
confidence: 97%
“…Low rates were reported multiple times in the Saudi literature in regards to awareness of smoking as a risk factor of CAD. [ 8 10 ] In a study conducted in the western region of Saudi Arabia, 66.7% of the population recognized smoking as a risk factor for CAD. [ 10 ] Furthermore, a recent study conducted in Jeddah reported an as low as 26% awareness regarding smoking as a risk for CAD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the risks and prevalence of CAD have been conducted for different cities in Saudi Arabia using cross-sectional methods, like studies in Qassim, Jeddah, Dawadmi, and Al-Qunfudah revealed that a large portion of the disease is associated with the diet of the population [7][8][9][10][11]. The sudden switch in dietary behavior from traditional to fast food severely impaired cardiovascular functions, causing them to become abnormal.…”
Section: Introductionmentioning
confidence: 99%